Peran Edukasi Manajemen Air Bersih pada Komunitas Pedesaan untuk Mitigasi Krisis Air di Kabupaten Sumbawa, NTB - Dian Rahayu; Agus Santioso; Rini Wijayanti (Lembaga Publikasi Ilmiah Nusantara, 2026)
Clean water scarcity remains a persistent risk in rural Indonesia, particularly in dryland regions such as Sumbawa Regency. This study examines the role of clean water management education in strengthening community capacity to mitigate local water crises. The research focuses on community-based educational interventions that integrate local knowledge, participatory learning, and practical management skills. The study applies a qualitative case study design with field observations, structured interviews, and document analysis involving village water user groups, local facilitators, and households. The analysis shows that education improves awareness, collective responsibility, and operational practices in rural water systems. Communities that receive structured education demonstrate better maintenance routines, stronger participation in decision making, and higher compliance with water use rules. Educational approaches rooted in local context support long term system functionality and reduce vulnerability to seasonal water stress. The findings confirm that education functions as a critical non-technical factor in rural water resilience. This study contributes empirical evidence to community managed water supply literature and supports policy alignment with Sustainable Development Goal 6 at the local level. The results offer practical guidance for rural water programs in water scarce regions.